(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study focused on the effectiveness of Social Media as a new Market for the Grade 12 ABM Students of Bestlink College of the Philippines school year 2021-2022. Most ABM Student students use sampling techniques for social platforms like Lazada, TikTok, etc. Social media is one of the mediums that can be used now. Social media is a website and application that enables users to create and share content or to participate in society. Therefore, social media as a new market is a sharing process involving two or more parties sending a message that each person easily understands. It can significantly contribute to a business and company’s success. Social media are open to all. This study revealed the effectiveness of social media has an impact by using social media platforms such as Lazada, TikTok, Lalamove, Shoppe, and Grab. This study revealed how brand awareness, purchase product, purchase product, sales, and promotion affect the social. This study reveals the effectiveness of social media and finds out that grade 12 ABM students know how to use social media as a new market.